2002
DOI: 10.1614/0890-037x(2002)016[0488:eopdrh]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Planting Date, Residual Herbicide, and Postemergence Application Timing on Weed Control and Grain Yield in Glyphosate-Tolerant Corn (Zea mays)1

Abstract: Studies were conducted in 1998 and 1999 in Ohio to determine the effect of postemergence (POST) application timing of glyphosate on weed control and grain yield in glyphosate-tolerant corn, and how this was influenced by corn planting date and the use of soil-applied herbicides. Glyphosate was applied based on giant foxtail height. Two applications of glyphosate provided better weed control than a single application, especially when applied to weeds 10 cm or less in early-planted corn. Yield was reduced occasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
98
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(113 citation statements)
references
References 7 publications
9
98
0
1
Order By: Relevance
“…A study by Rasmussen (2004) has revealed that plots sown at optimum time have shown more weed biomass as compared with delayed planting. Weed related yield loss in corn and soybean was significantly less when planting was delayed beyond optimum time, presumably due to depleted weed seed banks (Buhler and Gunsolus, 1996;Gower et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…A study by Rasmussen (2004) has revealed that plots sown at optimum time have shown more weed biomass as compared with delayed planting. Weed related yield loss in corn and soybean was significantly less when planting was delayed beyond optimum time, presumably due to depleted weed seed banks (Buhler and Gunsolus, 1996;Gower et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Management of weedsis considered to be an important factor for achieving higherproductivity. Due to increased cost and nonavailability of manuallabour in required quantity timely for hand weeding, role ofherbicide is significant preposition herbicides not only controlthe weeds timely and effectively but also offer great scope forminimizing the cost of weed control irrespective of situation.Use of pre and postemergence application of herbicides wouldmake herbicidal weed control more acceptable to farmers whichwill not change the existing agronomic practices but will allowfor complete control of weeds (Gower et al, 2002). Usage of pre-emergenceherbicides assumes greater importance in the view of theireffectiveness from initial stages.…”
Section: Introductionmentioning
confidence: 99%
“…Control of Xanthium strumarium was found to be greater than 90 per cent with glyphosate (Ferrell and Witt, 2002). Gower et al (2002) documented that, sequential post emergence applications of glyphosate were most effective for control of giant foxtail (95 per cent), Abutilon theophrasti and Chenopodium album (90 per cent) in late planted maize while in early planting of maize provided lower weed control. The same study observed, single application of glyphosate at 5 cm weed height rarely resulted in greater than 90 per cent control.…”
Section: Weed Control Efficiency Of Glyphosate Tolerant Maizementioning
confidence: 96%
“…Glyphosate application should be done before weeds attain 15 cm in height to avoid the yield losses. Reinfestation of weed after early post-emergence (EPOST) application had less potential to reduce yield than delaying application and allowing weeds to compete with corn for long period before removal (Gower et al, 2002). In northcentral USA the optimum timing for weed control to avoid maize grain yield loss for an initial application of glyphosate at four leaf stage when the weeds were less than 10 cm in height and not more than 23 days after corn planting (Cox et al, 2006).…”
Section: Time Of Poe Glyphosate Application In Transgenic Maizementioning
confidence: 99%